Suppressing the CDC37 cochaperone in hepatocellular carcinoma cells inhibits cell cycle progression and cell growth. (25th August 2014) - Wang, Zhanhui; Wei, Wei; Sun, Chris K.; Chua, Mei‐Sze; So, Samuel
Abstract Background & Aims The molecular cochaperone CDC37 regulates the activities of multiple protein kinases, and is an attractive broad‐spectrum target in many types of cancers in which it is over‐expressed. This study investigates the antitumour effects of inhibiting CDC37 in human hepatocellular carcinoma (HCC). Methods A total of 91 patients were enrolled for CDC37 mRNA detection by using quantitative real‐time PCR. Cell proliferation, gene expression changes and tumourigenicity were determined by targeting CDC37 using RNA interference in human hepatoma cell lines. Results We confirmed the significant over‐expression of CDC37 transcript and protein in HBV‐associated HCC patients. Using a CDC37‐specific small oligo‐siRNA, we silenced CDC37 expression in HepG2 and Huh7 hepatoma cell lines, and observed inhibition of in vitro cell proliferation, cell cycle arrest at the G1 phase, and enhanced apoptosis. Specifically, we found concomitant down‐regulation of Cyclin D1, CDK4, and pRB (S807/811 and S795) upon CDC37 suppression, which could mediate the arrest of cell cycle progression at the G1 phase. Gene expression profiling further identified several genes involved in cell proliferation, cell cycle progression, and apoptosis that are regulated by CDC37 suppression. Huh7 cells with stable knockdown of CDC37 showed decreased in vitro colony formation ability, and significantly slowed xenograft growth in vivo. Conclusions On the basis of the observed antitumour effects of inhibiting CDC37 expression, we propose that CDC37 is a promising therapeutic target in HCC. Its ability to regulate multiple pathways makes it potentially valuable in treating the heterogeneous subtypes of this malignancy.